MMP-8 single-nucleotide polymorphisms are related to ankylosing spondylitis in Chinese Han population. Issue 35 (August 2018) - Meng, Chenyang; Bai, Rui; Zhao, Zhenqun; Huang, Guimei; Jin, Tianbo; Feng, Wei; Liu, Wanlin
Abstract : Abstract: Ankylosing spondylitis (AS) is an extreme form of inflammatory arthritis which always leads to bony fusion of vertebral and chronic pain of back. A lot of genes including interleukin, matrix metalloproteinases (MMPs), and endoplasmic reticulum aminopeptidase were found associated with AS. MMP family members were involved in the autoimmune disease and orthopedic diseases such as rheumatoid arthritis and osteoarthritis, while few studies concentrated on the correlation between single-nucleotide polymorphisms (SNPs) in MMP and AS. In addition, there is no report on the relationship between MMP-8 and AS. To investigate the association between SNPs in MMP-8 and AS, we recruited 268 patients with AS and 654 healthy people to conduct a case–control study. Five SNPs including rs3740938, rs2012390, rs1940475, rs11225394, and rs11225395 of MMP-8 gene were genotyped. It was found rs3740938 of MMP-8 was associated with an increased risk of AS under the dominant model and additive model after adjustment for gender and age by performing logistic regression analysis (odds ratio [OR] = 1.49, 95% confidence interval [CI] = 1.02–2.18, P = .038; OR = 1.37, 95% CI = 1.01–1.87, P = .042, respectively). Moreover, haplotype "GGTCA" was associated with an increased risk of AS without adjustment for age and gender (OR = 1.75, 95% CI = 1.05–2.92, P = .032), while no positive result was found after adjustment for age and gender. Based on our results, our study indicates significant association between SNPs of MMP-8 and AS risk in a Chinese Han population and these results provide the first evidence that MMP-8 is correlated with AS.